2021
DOI: 10.3390/ijerph182010893
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Characterization and Physical Performance by Age and Biological Maturation in Young Tennis Players

Abstract: The objective was to analyze anthropometric and physical performance variables as a function of chronological age and biological maturity in young Chilean tennis players. The study was observational, cross-sectional, with descriptive and analytical characteristics. Eighty-seven tennis players were evaluated (58 men 15.1 ± 0.8 years and 29 women, 15.3 ± 0.8 years). The measured anthropometric variables were a sprint test of 20m; a modified agility test; a sit-and-reach test and shoulder flexibility; manual grip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 34 publications
3
11
1
4
Order By: Relevance
“…However, modern coaches focus not only on the technical aspects but also on nutritional strategies to reduce BF. This view is supported by recent studies on youth tennis players, which obtained BF and SMM values highly similar to ours [ 35 , 36 ]. Indeed, this evolution to a lower BF and endomorphy has also been observed in other sports, such as soccer [ 12 , 49 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, modern coaches focus not only on the technical aspects but also on nutritional strategies to reduce BF. This view is supported by recent studies on youth tennis players, which obtained BF and SMM values highly similar to ours [ 35 , 36 ]. Indeed, this evolution to a lower BF and endomorphy has also been observed in other sports, such as soccer [ 12 , 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…Luna-Villouta et al [ 35 ] also observed differences in BF and SMM percentages between a group of 58 male tennis players aged 15.4 ± 0.8 years and a group of 29 female tennis players aged 15.3 ± 0.8 years. These sex differences in body composition and somatotype were expected and have also been found between boys and girls of similar ages in other sports or in non-athlete populations [ 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, female players showed lower values when compared to the reference literature (165.4 ± 6.3 cm, 59.9 ± 6.2 kg, 21.9 ± 1.7 kg/m 2 , 16.3 ± 4.0/7.4 ± 2.6 mm and 27.0 ± 1.8/27.8 ± 1.7 cm) [ 38 ]. Furthermore, height and body mass values presented in the literature for males and females (174.2 ± 7.6, 64.3 ± 7.9, and 164.9 ± 3.7 cm, 50.1 ± 6.7 kg, respectively) [ 39 ] were also lower when compared with the current study. We verified in other studies that male players trained more hours per week than in this study (29.0 ± 6.7 h) [ 40 ], which can be attributed to age, sex, and level differences.…”
Section: Discussioncontrasting
confidence: 72%
“…Sobre los partidos, si bien estos varían sustancialmente en su volumen total de duración, se ha establecido un tiempo promedio aproximado de 1,5 horas para un partido de 2 o 3 sets. Por lo expuesto, es que este deporte es considerado de alta carga física (Fernandez, 2006;Kovacs, 2006;Luna-Villouta et al, 2021;Ulbricht et al, 2016).…”
Section: Introductionunclassified